2022
DOI: 10.1136/bmjopen-2021-058323
|View full text |Cite
|
Sign up to set email alerts
|

Psychological, social and financial impacts of COVID-19 on culturally and linguistically diverse communities in Sydney, Australia

Abstract: ObjectiveTo explore the psychological, social and financial outcomes of COVID-19—and the sociodemographic predictors of those outcomes—among culturally and linguistically diverse communities in Sydney, Australia.DesignCross-sectional survey informed by the Framework for Culturally Competent Health Research conducted between March and July 2021.SettingParticipants who primarily speak a language other than English at home were recruited from Greater Western Sydney, New South Wales.Participants708 community membe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The District's—and, in particular, our local champions'—strong ties to the community have strengthened the capacity of the Hub to access and involve community members in the co‐creation of health literacy research. In addition to Parenting Plus, another recent example of this was the rapid mobilization of staff and consumers in Western Sydney and two adjoining health districts to co‐design and conduct the largest Australian COVID‐19 survey of people who speak a language other than English at home 42,43 …”
Section: Methodsmentioning
confidence: 99%
“…The District's—and, in particular, our local champions'—strong ties to the community have strengthened the capacity of the Hub to access and involve community members in the co‐creation of health literacy research. In addition to Parenting Plus, another recent example of this was the rapid mobilization of staff and consumers in Western Sydney and two adjoining health districts to co‐design and conduct the largest Australian COVID‐19 survey of people who speak a language other than English at home 42,43 …”
Section: Methodsmentioning
confidence: 99%
“… 36 A study conducted on psychological, social and financial impacts of COVID-19 on culturally and linguistically diverse communities, concluded that changes in financial status, resulted in reduction in meeting family expenses for better living. 37 Whilst these findings reiterate the pervasive financial burden for patients with T2DM to maintain healthy eating habits as self-management, financial burden has serious implications on economy and food security for South African citizens at large.…”
Section: Discussionmentioning
confidence: 99%
“…Deeper than the physical restrictions were the affective responses of residents who felt unfairly targeted when compared with other Sydney LGAs, the idea of “second class citizens” gained currency in the media (Hayman, 2022) and aligned with findings in social research (Mude et al, 2021; Muscat et al, 2022). During daily COVID‐19 briefings to the public, patronising and culturally insensitive remarks were routinely made about sociocultural and ethno‐religious norms that may be exacerbating the spread of the Delta variant, slowing vaccination uptake.…”
Section: Peak Pandemic: Apps and Qr Codesmentioning
confidence: 97%